Improving Understanding of Marine Ecosystems Through Thematic Programs at Tonasa Elementary School, Tonasa Village - Surur, Fadiyah Rahimi; Husain, Firman (Faculty of Engineering UNHAS, 2025)
The program on the introduction and importance of the ocean is part of the Thematic Community Service Program (KKN) conducted by Universitas Hasanuddin students in Tonasa Village. This program aims to enhance young students' understanding of marine ecosystems, their benefits, and the impacts of ecosystem imbalance. Based on initial surveys, schools in this area lack access to teaching materials about the ocean. The methods employed include interactive material delivery, Q&A sessions, and creative activities such as coloring. Evaluation results showed an improvement in students' understanding, with average post-test scores of 76 for fifth grade and 84 for sixth grade, compared to pre-test scores of 58 and 64, respectively. This creative approach not only increased learning motivation but also instilled values of responsibility toward marine conservation. This program is expected to lay the foundation for the younger generation to contribute to preserving marine ecosystems as a vital part of life.